Turner syndrome – The clinical spectrum and management dilemmas. Issue 4 (21st June 2018) - Thayalan, Krishanthy; Chung, Kimberly; Kothari, Alka
Abstract: Introduction: Turner syndrome (TS) is a common sex chromosome disorder, with a varied clinical spectrum and prognosis. It may range from the complete phenotype of TS characterised by short stature, ovarian failure, cardiac and renal abnormalities, with milder variants often associated with mosaic TS. Materials and Methods: We describe five cases of TS. Results: In case 1, complete TS was identified by first‐trimester screening with a grossly oedematous fetus at 11 weeks of gestation and underwent medical termination of pregnancy due to the dismal prognosis. In case 2, a hydropic fetus and large cystic hygromas were identified at routine second‐trimester morphology scan. Intra‐uterine fetal death was identified at 22 weeks of gestation and formal karyotype confirmed complete TS. Case 3 demonstrates the potential for a successful live birth of mosaic TS with mild neurocognitive and renal abnormalities. Case 4 demonstrates the ability for TS to go undetected until adolescence where the patient was diagnosed at 15 years of age during investigations for severe anaemia, identified as secondary to critical aortic stenosis and Heyde's syndrome. Case 5 highlights the potential for patients with TS to reproduce with assisted reproductive technology. Discussion: These cases explore the prognostic spectrum of TS and highlight that they have a potential to lead productive and fulfilling lives. Conclusion: Consequently, a multimodal risk stratification approach to prognostic counselling should be under‐taken with consideration of pertinent history, major sonographic abnormalities, maternal serum testing and invasive testing.